A privacy-aware feature selection method for solving the personalization–privacy paradox in mobile wellness healthcare services. Issue 5 (1st April 2015) - Lee, Namyeon; Kwon, Ohbyung
Highlights The essence of personalization in mobile wellness healthcare (MWH) services is feature selection. A novel method of privacy-aware feature selection for individualized MWH is presented. An optimal set of features is automatically found to solve the personalization–privacy paradox. The results successfully show that the proposed method outperforms conventional methods.